Selecting red blood cell units to perform RBCX in patients with sickle cell disease. (April 2019) - Raba, M.
Abstract: Red blood cell exchange (RBCX) is a standard option for treating or preventing complications in patients with sickle cell disease (SCD). According to the patient's blood volume, the amounts of red blood cells (RBC) to be exchanged and the practices of the apheresis and clinical teams, such treatment requires numerous red blood cell units (RBCUs) (3–15 RBCUs per procedure). To perform RBCXs safely and prevent the risk of alloimmunization, appropriate RBCUs must be selected and transfused to replace the sickled RBCs. Understanding of alloimmunization in patients with SCD strengthened the development of recommendations for preventing the risk of alloimmunization. This review describes the alloimmunization risk, the methods used to decrease the risk, and our own experience.